Conventional Construction and 3D Printing: A Comparison Study on Material Cost in Jordan - Rawan Allouzi; Wael Al-Azhari; Rabab Allouzi (Journal of Engineering)
Three-dimensional (3D) printing is a procedure used to create 3D objects in which consecutive layers of a material are computer-controlled produced. Such objects can be constructed in any shape using digital model data. First, this paper presents a state-of-the-art review of the advances in 3D printing processes of construction. Then, the architectural, economical, environmental, and structural features of 3D printing are introduced. Examples of 3D printed structures are presented, and the construction challenges facing Jordan, that encouraged this study, are stated. Finally, a precise description regarding the impact of 3D printing is provided by comparing conventional construction data of Ras Alain Multipurpose Hall in Jordan and the expected data if the same building has been built using 3D printing. The suggested model is generated using Revit software. As a result of this study, an understanding of 3D printing procedure, mechanism of action, and its impact on the future of construction and architecture through economical, structural, and environmental parameters is achieved. This leads to encourage engineers and contractors to take this subject into account for construction in Jordan.